Design of Optimal SMES Controller Considering SOC and Robustness for Microgrid Stabilization - Ngamroo, Issarachai; Vachirasricirikul, Sitthidet (My University, 2016)
The microgrid with wind and photovoltaic (PV) power sources unavoidably encounters the power fluctuation problem. To solve this problem, the superconducting magnetic energy storage (SMES) can be used. Nevertheless, large power fluctuation from wind and PV sources, and severe system faults may cause the overcharge or deep-discharge state of SMES. These abnormal states highly degrade the dynamic performance of the SMES. To handle these situations, this paper concentrates on the new SMES power controller design considering state-of-charge (SOC), robustness, and optimal inductance of the superconducting coil for microgrid stabilization. The active and reactive power controllers of SMES are represented by the proportional-integral (PI) control. The SOC deviation control and the mixed H2/H∞ control are proposed to optimize the SMES coil inductance and PI parameters. Simulation study is performed to signify the control effect of the proposed SMES.
Keywords: Microgrid; optimization; power fluctuation; state-of-charge (SOC); superconducting magnetic energy storage (SMES)